FOODS CONTAINING FORMALIN AND CHLORINE IN THE EAST SURABAYA AREA - Sherly Dwi Agustiningrum; Nita Kusuma Wardani; Neshia Nurindah Alifianti (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Safe and nutritious food is very important for our body. Unfortunately not all foods meet food safety requirements. Some traders use prohibited food additives such as formalin and chlorine. Increasing competition and desire to increase financial benefits make some traders use that way. Therefore this study was conducted to provide an overview of the situation of illegal use of food additives. The results of the study are expected to be used as a reference for the Government to control the use of food additives in Indonesia. The purpose of this study is to identify foods containing formalin and chlorine in East Surabaya Area. Methods: This descriptive-observational research use purposive sampling technique. The samples consist of 16 foods for formalin test and 16 foods for chlorine test. It is obtained from food traders suspected of selling food containing those substances in East Surabaya. Tests were conducted in the Environmental Health Laboratory of Universitas Airlangga Surabaya. Formalin and chlorine tests are carried out qualitatively, using test kits to see the formalin content and color reaction test to see the chlorine content. The results of data analysis is presented descriptively in the form of table and figure. Results: The results show 12.5% samples (salted fish and white tofu) are containing formalin. While chlorine test results show 75% samples (white cracker, rice, noodle, salt, wheat flour, white tofu and tea dye samples) are positive of chlorine. Conclusions: There are some foods containing formalin and chlorine in East Surabaya area. Health institutions are advised to conduct regular inspection and investigation of food content. In addition, regular education and coaching needs to be done to food vendors to improve their knowledge regarding the use of formalin and chlorine.